Knowledge of intensive care nurses on evidence based guidelines for prevention of ventilator associated pneumonia - Gomes, Viviana Paula (My University, 2010)
The purpose of this study was to determine the knowledge of nurses working in ICU with respect to evidence based guidelines for prevention of ventilator associated pneumonia. A non experimental, descriptive, correlational and contextual two phase research design was used. The first phase of the study consisted in validating the data collection instrument for applicability to the South African context. The second phase of the study used the instrument validated in phase one to test the knowledge of nurses working in ICU. Data analysis was done by means of descriptive and inferential statistics using frequency distributions, cross-tables, means, standard deviations and Pearson correlation coefficient. The knowledge of 83 nurses working in ICU from two hospitals of the private health sector and one hospital of the public health sector in Gauteng was tested using the data collection instrument validated by ICU nursing experts. Knowledge of ICU trained and non ICU trained nurses working in ICUs of the three hospitals was found to be lacking in the evidence based guidelines for prevention of ventilator associated pneumonia. Of the 83 participants, 18 (21.69%; CI 95% 13.4% ; 32.1%) achieved a pass mark of 70% on the multiple choice part of the questionnaire and were considered to have adequate knowledge on the evidence based guidelines for prevention of VAP. The mean score of participants was 4.25 (SD 1.537 CI 95% 3.92; 4.59) on nine questions. The difference in the mean average score of ICU trained nurses and non ICU trained nurses was very similar demonstrating no statistically significant difference in the knowledge of the two groups of nurses. A weak correlation between years working in ICU and knowledge was found, but this correlation may be clinically insignificant. Recommendations to address this lack of knowledge of ICU nurses were given for clinical nursing practice, nursing education as well as for nursing research.
MSc (Nursing), Faculty of Health Sciences, University of the Witwatersrand
Keywords: ventilator; pneumonia; nursing experience